Model rainfall-runoff in the constraints Amazon - Casavecchia, Bruno Henrique; Almeida, Frederico Terra de; Souza, Adilson Pacheco de; Zolin, Cornélio Alberto; Uliana, Eduardo Morgan; Marques, Adriana (Ciência e Natura, 2018)
The aim of this study was based on different samples of settings for calibration and validation of IPH II model, using limited historical series of data of daily average water flow registered in Caiabi river hydrologic basin, a tributary stream of Teles Pires river- Mato Grosso. The total area of the study location is 440.98 km2, and there were installed three meteorological automatic stations for climate monitoring, and one linigraph in the basin end for monitoring the altimetric quotas and also to estimate the daily water flow of the river. The precipitation data, evapotranspiration and water flow used to feed the IPH II model were collected between 09/18/2015 and 04/30/2016, using sixty percent of the initial historical data to calibrate and forty percent to validate the model has shown better statistic performance, however rearranging the data and establishing the sixty percent of the central data for the calibration was verified that there was an increase in the statistical performance of the model making the simulations of the IPH II model were successful. It was indicated by the results that the sample methodology for calibration of hydrologic models can bring substantial improvement to the performance